Distributed energy efficient unequal clustering algorithm for wireless sensor networks - SHANG Feng-jun1; Mehran Abolhasan2; Tadeusz Wysocki3 (Tongxin xuebao)
A distributed energy-efficient unequal clustering （DEEUC） algorithm was proposed for wireless sensor net-works by research current routing algorithms. The core of DEEUC has three parts. Firstly, when tentative clusterheads are selected, an average energy factor was introduced to balance the residual energy of the whole network nodes so that it may improve the network energy efficiency. Secondly, an energy consumption ratio function was proposed to balance energy-efficient of each node. Finally, an unequal clustering algorithm was proposed for single-hop homogeneous networks. Through both theoretical analysis and numerical results, it is shown that DEEUC prolongs the network lifetime significantly against the other clustering protocols such as LEACH-C and EECS. Under general instance, DEEUC may prolong the lifetime up to 30% against EECS.